Computational modeling of the axial behavior of corroded and buckled short steel piles strengthened using concrete-filled GFRP jackets. (May 2023) - Cosgun, S.I.; Kaya, A.; Gencturk, B.
Highlights: A new finite element modeling strategy has been proposed for buckled and corroded steel piles. A new repair strategy composed of concrete-filled GFRP tubes has been investigated. Rapid strengthening approach was found to be very effective in restoring original capacity. Proposed modeling approach could predict complex failure modes. Abstract: Steel columns or piles commonly used in bridges and marine structures in various parts of the world exhibit insufficient strength due to increased load demands or section loss due to corrosion. The latter issue can cause unexpected buckling of these columns. In this study, the repair of corroded and buckled short steel piles using concrete-filled GFRP jackets was numerically simulated to better understand the overall effectiveness of the method and the influence of the parameters involved. Thirteen steel piles used in this study had different degradation characteristics to investigate the section losses affecting the axial capacity and failure modes. The parameters considered included the presence or absence of concrete steel reinforcement (rebar), the diameter of the rebar, the number of GFRP layers, the location of the worn zone in the steel section and the severity of the section loss. The numerical models were validated using these experimental results of the repaired specimens from the authors' earlier work on the topic. The main contribution of this study is in the development of the numerical models that can very accurately simulate the ultimate strength and damage behavior of retrofitted piles that are heavily corroded and buckled. The validated models were used in a parametric study to understand the effects of different levels of concrete strength, or corrosion of the piles in the flanges, the web, or both. The results of the parametric study provided further understanding of the structural behavior of degraded and strengthened steel piles.